The effect of BMP2/Smads pathway mediating platelet-rich fibrin on rat bone mesenchymal stem cells - Wu, L-L; Jia, Y-M; Sui, Y-X; Ao, S; Wang, Y; Liu, Y; Xu, W-D; Zhang, H-B; Zhang, H; Mao, J-H; Yang, X-T; Leng, H (European review for medical and pharmacological sciences, 2022)
We explored the influences on platelet-rich fibrin (PRF) to rat Bone Mesenchymal Stem Cells (BMSCs), as well as the role of bone morphogenetic protein 2 (BMP2)/maternal signal protein homolog (Smads) pathway.OBJECTIVEWe explored the influences on platelet-rich fibrin (PRF) to rat Bone Mesenchymal Stem Cells (BMSCs), as well as the role of bone morphogenetic protein 2 (BMP2)/maternal signal protein homolog (Smads) pathway.The proposed research is approved by the ethics board of the Second Affiliated Hospital of Harbin Medical University. The BMSCs were isolated and purified. The BMSCs were assigned to a control group arbitrarily, PRF group, BMP activator group and BMP inhibitor group (hereinafter referred to as activator group and inhibitor group). Each group of BMSCs in the logarithmic growth phase was detected for the alkaline phosphatase (ALP) activity since 3 days and 14 days of culture; CCK-8 assay was conducted for detection of the proliferation of BMSCs; Real time PCR was conducted for detection of the osteogenic differentiation marker collagen I (COL-I), BMP2, Runt-related transcription factor 2(RUNX2), osteocalcin (OCN) mRNA relative expression levels; Western-Blot detection of BMP2, OCN, P-SMAD1/5/8, relative expression level of RUNX2 protein.MATERIALS AND METHODSThe proposed research is approved by the ethics board of the Second Affiliated Hospital of Harbin Medical University. The BMSCs were isolated and purified. The BMSCs were assigned to a control group arbitrarily, PRF group, BMP activator group and BMP inhibitor group (hereinafter referred to as activator group and inhibitor group). Each group of BMSCs in the logarithmic growth phase was detected for the alkaline phosphatase (ALP) activity since 3 days and 14 days of culture; CCK-8 assay was conducted for detection of the proliferation of BMSCs; Real time PCR was conducted for detection of the osteogenic differentiation marker collagen I (COL-I), BMP2, Runt-related transcription factor 2(RUNX2), osteocalcin (OCN) mRNA relative expression levels; Western-Blot detection of BMP2, OCN, P-SMAD1/5/8, relative expression level of RUNX2 protein.In contrast to the control group, BMSCs' the ALP activity of the PRF group, activator group, as well as inhibitor group increased for 3 days and 14 days, and the activator group>PRF group>inhibitor group (p≤0.05). ALP activity in each group was elevated with the increase in culture time, the ALP activity of the control group, PRF group, activator group and inhibitor group increased (p≤0.05). In comparison to the control group, the relevant expression levels of COL-I, BMP-2, RUNX2 and OCN in the PRF group, activator group, and inhibitor group increased, and the activator group>PRF group>inhibitor group (p≤0.05). The relative expression levels of BMP2, OCN, p-SMAD1/5/8 and RUNX2 protein in each group were statistically different, the activator group>PRF group>control group>inhibitor group (p≤0.05).RESULTSIn contrast to the control group, BMSCs' the ALP activity of the PRF group, activator group, as well as inhibitor group increased for 3 days and 14 days, and the activator group>PRF group>inhibitor group (p≤0.05). ALP activity in each group was elevated with the increase in culture time, the ALP activity of the control group, PRF group, activator group and inhibitor group increased (p≤0.05). In comparison to the control group, the relevant expression levels of COL-I, BMP-2, RUNX2 and OCN in the PRF group, activator group, and inhibitor group increased, and the activator group>PRF group>inhibitor group (p≤0.05). The relative expression levels of BMP2, OCN, p-SMAD1/5/8 and RUNX2 protein in each group were statistically different, the activator group>PRF group>control group>inhibitor group (p≤0.05).PRF can promote the proliferation and osteogenic differentiation of BMSCs by activating the BMP2/Smads signaling pathway.CONCLUSIONSPRF can promote the proliferation and osteogenic differentiation of BMSCs by activating the BMP2/Smads signaling pathway.